Executive Functioning and the Metabolic Syndrome: A Project FRONTIER Study - Falkowski, Jed (Oxford University Press, 2014)
Decrements in cognitive functioning have been linked to the metabolic syndrome (MetS), a risk factor for cardiovascular disease defined by the presence of three of the following: elevated blood pressure, increased waist circumference, elevated blood glucose, elevated triglycerides, and low high-density lipoprotein cholesterol. We examined the relationship between four measures of executive functioning (EF) and MetS as diagnosed by National Heart, Lung, and Blood Institute-American Heart Association criteria. MetS was examined in a rural population of 395 persons with a mean age of 61.3 years, 71.4% women, 37.0% Hispanic, 53.7% White non-Hispanic. There was a 61.0% prevalence of MetS. We derived a factor score from the four executive function measures which was used to compare those with and without the syndrome, as well as any additive effects of components of the syndrome. Those with MetS exhibited significantly poorer performance than those without the syndrome. However, there was no additive effect, having more components of the syndrome was not related to lower performance. The presence of MetS was associated with poorer EF in this rural cohort of community dwelling volunteers.